2020
DOI: 10.3390/cells9122716
|View full text |Cite
|
Sign up to set email alerts
|

Histone Variant H3.3 Mutations in Defining the Chromatin Function in Mammals

Abstract: The systematic mutation of histone 3 (H3) genes in model organisms has proven to be a valuable tool to distinguish the functional role of histone residues. No system exists in mammalian cells to directly manipulate canonical histone H3 due to a large number of clustered and multi-loci histone genes. Over the years, oncogenic histone mutations in a subset of H3 have been identified in humans, and have advanced our understanding of the function of histone residues in health and disease. The oncogenic mutations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 162 publications
(176 reference statements)
0
7
0
Order By: Relevance
“…Thus, these mutated histones are referred to as oncohistones [ 69 ]. The incorporation of mutant H3.3 (an oncohistone) in which the altered amino acids change PTMs could impact chromatin properties of the broad epigenetic domain and alter expression of genes with the broad epigenetic domain, contributing to diseases associated with H3.3 mutants [ 69 , 70 ].…”
Section: Chromatin Dynamics Of Broad Epigenetic Domainsmentioning
confidence: 99%
“…Thus, these mutated histones are referred to as oncohistones [ 69 ]. The incorporation of mutant H3.3 (an oncohistone) in which the altered amino acids change PTMs could impact chromatin properties of the broad epigenetic domain and alter expression of genes with the broad epigenetic domain, contributing to diseases associated with H3.3 mutants [ 69 , 70 ].…”
Section: Chromatin Dynamics Of Broad Epigenetic Domainsmentioning
confidence: 99%
“…Several studies in animals (Drosophila and mammals) have explored the effect of mutations at Lysine residues in Histone 3, providing powerful tools to interrogate their roles in vivo . Such analyses were extensively done for H3K4, K36 and K27 (Trovato et al ., 2020). In particular, the Lysine-to-Methionine substitution at K27 shows a dominant phenotype due to its prevailing inhibitory effect on PRC2 HMT (Chan et al ., 2013)(Herz et al ., 2014)(Fang et al ., 2018), thereby contributing to better understand the structural basis of H3K27me3 spreading (Justin et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Lysine-to-Methionine substitution at K27 shows a dominant phenotype due to its prevailing inhibitory effect on PRC2 HMT (Chan et al ., 2013)(Herz et al ., 2014)(Fang et al ., 2018), thereby contributing to better understand the structural basis of H3K27me3 spreading (Justin et al ., 2016). Some other studies have used more neutral substitutions with amino acids such as Alanine, revealing interesting effects on gene regulation and development (Pengelly et al ., 2013)(Leatham-Jensen et al ., 2019)(Zhang et al ., 2019)(Gehre et al ., 2020) (Trovato et al ., 2020). In contrast, a limited amount of studies reported similar approaches in plants (Iwakawa et al ., 2017)(Sanders et al ., 2017)(Lu et al ., 2018)(Yan et al ., 2020)(Lin et al ., 2018) and none of them characterized the effect of a single amino acid substitution at K27 of the ubiquitous H3 proteins, on plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the functional study of individual histone PTMs presents formidable challenges, and in most organisms can only be indirect. For instance, gene-editing approaches in mammals and other metazoans are extremely demanding because canonical histones are encoded by multiple genes, making it difficult to selectively interfere with specific PTMs [ 56 ]. This paper provides a proof of concept for a new method to address these questions.…”
Section: Discussionmentioning
confidence: 99%